Guía psicoeducativa para la prevención de conductas adictivas en adolescentes de 12 a 15 años del Instituto Tecnológico “Los Shyris” - Quiroga Ramírez, Sandy Nataly (2014)
This thesis aims to design a psychoeducational Guide for prevention of addictive behaviors in adolescents 12 to 15 years Institute of Technology " The Shyris " , which pretend to be a tool for the teacher , the management process , implementation and control will be easy to use , with a humanist vision where they were to achieve full participation allowing stimulate , educate and strengthen the participation of the " Players" , which are what make all levels of education systems ( education community ) , so they can be observers , critics and participate daily in a timely prevention of addictive behaviors. This guide is a reference for the best institutional development in the field of prevention, as it will allow teachers, students, parents and the educational community in general go for proper and adequate information on addictive behaviors.